Computation of Constant Gain and NF Circles for 60 GHz Ultra-low noise Amplifiers - Gnanamani, Christina; Pandiaraj, Shanthini (IRO Journal on Sustainable Wireless Systems, 2021)
Wireless communication is a constantly evolving and forging domain. The action of the RF input module is critical in the radio frequency signal communication link. This paper discusses the design of a RF high frequency transistor amplifier for unlicensed 60 GHz applications. The Transistor used for analysis is a FET amplifier, operated at 60GHz with 10 mA at 6.0 V. The simulation of the amplifier is made with the Open Source Scilab 6.0.1 console software. The MESFET is biased such that Sll = 0.9<30°, S12 = 0.21<-60°, S21= 2.51<-80°, and S22 = 0.21<-15o. It is found that the transistor is unconditionally stable and hence unilateral approximation can be employed. With these assumptions, the maximum value of source gain of the amplifier is found to be at 7.212 dB and the various constant source gain circles and noise figure circles are computed. The transistor has the following noise parameters: Fmin = 3 dB, Rn = 4 Ω, and Γopt = 0.485<155°. The amplifier is designed to have an input and output impedance of 50 ohms which is considered as the reference impedance.